(untitled) (Research, Society and Development, 2020)
The purpose of this study is to present, in a timely manner, a brief approach on normative aspects and preventive coping practices for women victims of domestic violence and its main psychological repercussions, identifying the possible disorders caused by the aggression and its consequences. Domestic violence is considered as an act resulting from a patriarchal culture, reproduced for centuries, causing suffering and anguish to the victims who are permeated in the various layers of society. In this study, the context of the invisibility of domestic violence will be addressed, in addition to aspects related to the application of the Maria da Penha Law (LMP). To achieve the objectives of the study, a bibliographic review was made, through articles indexed in the databases, SCIELO and BSV. For this study, the following descriptors were adopted: violence, Maria da Penha Law, woman. Domestic violence is a phenomenon that has affected the lives of many women for centuries. This fact is of great concern, since several women are beaten, killed or end up suffering some type of psychological disorder through this abuse. In the course of the research, it is possible to verify what domestic violence is, then consolidating this struggle through the Maria da Penha Law, being reinforcing elements to reduce abuse against women, who had long been in the invisibility field for a long time.